Human-pet Relationship, Pet Abandonment, and Clinical Correlation for Patients Infected with Dermatophytosis of the Glabrous Skin - Sombatmaithai S. (2023)
Objective: The study on human-pet relationship and pet abandonment among dermatophytosis patients is limited. This study aims to review these correlations. Materials and Methods: A two-year retrospective cross-sectional study was conducted. Case record forms were reviewed for clinical manifestations, fungal identification, human-pet relationships, and changes in the relationships after dermatophytosis diagnosis. Results: A total of 230 dermatophytosis patients from the Dermatology outpatient clinic, Siriraj Hospital, were included. The mean age was 41.9 ± 19.1 years and 51.3% were female. Among 170 cases with positive fungal culture, zoophilic dermatophytosis from M. canis infection was identified in 15.9% which was predominately found in females and manifested as shorter duration of onset, and higher involvement on exposed areas when compared to anthropophilic dermatophytosis. Most (71%) of patients with M. canis infection classified themselves as pet-lovers. The relationship with pets had changed after the dermatophytosis diagnosis in 41% of them which was statistically different from 8.8% in non-pet lovers (P = 0.001). The overall pet abandonment rate was 26.6%. The abandonment rate was 40.9% among non-pet lovers, while 30.6% was reported among pet lovers. Conclusion: Zoophilic M. canis infection was associated with rapid onset and on predominant-exposed areas. Some pets could be asymptomatic, so identification of the reservoirs of dermatophytosis is important in the treatment process and helps prevent future recurrence. Paying attention to human-pet relationships and pet abandonment is critical. Knowledge about dermatophytosis transmission, and appropriate pet management should be advised to decrease abandonment